Recent Intensified Winter Coldness in the Mid-High Latitudes of Eurasia and Its Relationship with Daily Extreme Low Temperature Variability - Chuhan Lu; Shaoqing Xie; Yujing Qin; Jiewen Zhou (Advances in Meteorology)
Observational records in recent decades show a large-scale decrease in the cold-season temperature variance in the Northern Hemisphere midlatitudes under continuous global warming. However, severe low temperature events in winter frequently occurred in midlatitude Eurasia (MEA) in the last decade. Here, we define a new coldness intensity (CI) index for the near-surface based on the amplitude of daily anomalously cold temperatures in winter to demonstrate the CI of the variability of low temperature extremes. The results show that a sign-consistent mode dominates the CI variation in MEA, with a marked intensification during the last decade via empirical orthogonal function (EOF) analysis. This leading mode is significantly related to the frequency of winter extreme events. The associated circulations are characterized by a remarkable anomalous anticyclone in Northwest Eurasia, which induced substantial cold advection in MEA. The widespread intensified CI in MEA is closely linked with strong surface anticyclones and synoptic blocking in the mid-high latitudes (25°E–85°E). Coincidently, positive phase shifts of the first two leading modes of the extratropical circulation, which feature similar blocking-like anomalies in the northwestern Eurasian subarctic, jointly play an important role in the recent frequency of severe winters.